The relationship between vertical jump and sprint performance between different positions among football players / Mohammad Arif Abu - Abu, Mohammad Arif (2019)
Fitness component are very crucial component in sport such as power and speed. In football, power and speed were highly occurring to commit with the high pace of game pattern. The main purpose of this study was to determine the relationship between vertical jump and sprinting performance in different positions among football players. Subjects were consisted of 30 football players from Sekolah Menengah Kebangsaan Seri Ampangan, Negeri Sembilan. Subjects were divided into three groups: forward, midfielder and defender. The test that involved were Sargent Jump test and 30-meter sprint test. It was found that there was high relationship between power and speed performance (r=-0.85, p=O.OO). This study also found significant differences in power performance between positions (M=5598.22, SD=1144.58) and also significant differences in speed performance between positions (M=4.86, SD=O.49) with forward players tend to have the highest power production which is (M=6233.19, SD=750.80) followed by defender (M=6125.87, SD=726.23) and midfielder (M=4435.61, SD=933.30). For speed performance, forward shows the greatest performance (M=4.49, SD=0.35) tracked by defender (M=4.83, SD=O.41) and midfielder (M=5.26, SD=O.4O). Implications from this study might provide beneficial for coaches for the assessment of performance for their players and deliver the training method efficiently.